Comparative Performance Analysis of Nutrient and pH Control in Hydroponic Systems Using Coupled and Decoupled Methods - Ina Rahmawati Putri; Bambang Siswojo; Mochammad Rusli (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2026)
pH and TDS are critical parameters in hydroponic systems that directly influence plant growth. This research develops an automatic control system for nutrient solution and pH regulation in hydroponic cultivation using a PID controller implemented with both coupled and decoupled methods. The aim of the research is to evaluate the performance differences between these two control approaches and to contribute to the development of more accurate and adaptive strategies for maintaining nutrient solution quality. Lettuce plants were used as test subjects with target conditions of 550 ppm TDS and pH 6.5. The research was conducted through MATLAB simulations and hardware implementation to assess system performance. The simulation results indicated that the decoupled method provides superior performance, achieving a pH rise time of 6.04 s, a settling time of 31.24 s, an overshoot of 9.5%, and zero steady-state error. The TDS response exhibits a rise time of 84.97 s, a settling time of 161.67 s, zero overshoot, and zero steady-state error. Hardware implementation demonstrates similar trends, with a pH rise time of 8.34 s, a settling time of 11 s, zero overshoot, and a steady-state error of 0.90%. The TDS response shows a rise time of 30.7 s, a settling time of 36 s, an overshoot of 4.36%, and a steady-state error of 0.60%. In contrast, the coupled method produces slower responses, longer settling times, and higher steady-state errors. Overall, the decoupled method proves to be more effective and responsive in maintaining pH and nutrient stability, demonstrating strong potential for application in smart agriculture systems.